Bioenergy from wastewater in a microbially-charged redox flow cell - Santos, Márcia S. S. (2018)
Wastewater is a valuable renewable energy source to generate newest approaches for electrochemical energy conversion in bioelectrochemical system (BES) for energy storage devices. A BES to generate a bio-charging redox pair to be use as negalyte in a redox flow cell (RFC) was study. In BES 2,6-antraquinone was introduced as new redox pair (catholyte), where wastewater mixed communities were the anolyte for the generation of a bio-charged redox pair. The BES results indicated the reduction of the quinone (ca. 50 %), promoting power density ca. 10 mW m-2. A RFC with the bio-charged redox pair as negalyte and potassium hexacyanoferrate (III) as posilyte was tested, reaching ca. 100 % of coulombic efficiency, with potential and energy efficiencies ca. 60 %. Wastewater in the new microbiallycharged redox flow cell generate a clean energy that can be stored in a new landmark system.